Exposure to violence and low family income are associated with heightened amygdala responsiveness to threat among adolescents. (December 2019) - White, Stuart F.; Voss, Joel L.; Chiang, Jessica J.; Wang, Lei; McLaughlin, Katie A.; Miller, Gregory E.
Highlights: Processing of emotional facial expressions is important for social functioning. Low socio-economic status impacts processing of emotional faces. Exposure to violence impacts processing of emotional faces. Amygdala response to angry faces positively correlated with both. Multiple pathways to increased amygdala responsiveness exist. Abstract: The processing of emotional facial expressions is important for social functioning and is influenced by environmental factors, including early environmental experiences. Low socio-economic status (SES) is associated with greater exposure to uncontrollable stressors, including violence, as well as deprivation, defined as a lack or decreased complexity of expected environmental input. The current study examined amygdala and fusiform gyrus response to facial expressions in 207 early adolescents (mean age = 13.93 years, 63.3% female). Participants viewed faces displaying varying intensities of angry and happy faces during functional MRI. SES was assessed using the income-to-needs ratio (INR) and a measure of subjective social status. Cumulative exposure to violence was also assessed. When considered in isolation, only violence exposure was associated with heightened amygdala response to angry faces. When considered jointly, violence exposure and lower INR were both associated with increased amygdala response to angry faces and interacted, such that lower INR was associated with increased amygdala reactivity to anger only in those youth reporting no exposure to violence. This pattern of findings raises the possibility that greater amygdala reactivity to threat cues in children raised in low-SES conditions may arise from different factors associated with an economically-deprived environment.